GT 10 - fashion, sustainability and inclusion (Revista de Ensino em Artes, Moda e Design, 2022)
Interview with the coordinators of GW Fashion, Sustainability and Inclusion, held between June and July 2022 from Caxias do Sul (RS) and Londrina (PR).
Keywords: Fashion; Sustainability Inclusion